(3WHbGJ GdTGaYjI GdcHQis - (3YHO GdhgGH Hf Ydj Hf YHO GdcGaj GdSHcj, CHh fUQ , JGL GdOjf , J (B771 (3g` s
(3ChdgG (B:s
(3JQLeI Ydi Hf GdbGSe Hf GdeXaQ Hf Ydi Hf GdSgQhOi ef Cgd GdehUd s
(3BNQgG (B:s
(3BNQ GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B225s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B89 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B171 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1101s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs